Enhanced Catalytic Activity of Boron Nitride Nanotubes by Encapsulation of Nickel Wire Toward O2 Activation and CO Oxidation: A Theoretical Study - Mao, Keke; Lv, Haifeng; Li, Xiuling; Cai, Jiajia (Frontiers in Chemical Engineering, 2022)
Perfect boron nitride (BN) nanotubes are chemically inert, and hardly considered as catalysts. Nevertheless, metal wire encapsulated BN nanotubes show extraordinarily high chemical activity. We report nickel (Ni) nanowire encapsulated BN(8,0) and BN(9,0) nanotubes toward O2 activation and CO oxidization on the basis of first-principles calculations. Our results suggest that Ni wire encapsulated BN(8,0) and BN(9,0) nanotubes can easily adsorb and activate O2 molecules to form peroxo or superoxo species exothermically. Meanwhile, superoxo species are readily to react with CO molecules forming OCOO intermediate state and finally yielding CO2 molecules. Meanwhile, the rate-limiting step barrier is only 0.637 eV, implying excellent performance for CO oxidation on Ni nanowire encapsulated BN nanotubes. This study provides a practical and efficient strategy for activating O2 on metal encapsulated BN nanotube toward CO oxidation.